PELAKSANAAN KOORDINASI DINAS KEHUTANAN KABUPATEN ROKAN HILIR DALAM UPAYA PENCEGAHAN KEBAKARAN HUTAN DAN LAHAN - Fitra, Asbeni Mai; Yuliani, Febri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
Abstract this research is writing about the coordination in the prevention offorest fires and forest service lands in Rokan Hilir. This essay brought upon bythe high level of land and forest fires in the Rokan Hilir. This is an essay thatwas taken based on the performance problems of coordination of ForestryAgency of Rokan Hilir (Dinas Kehutanan Rokan Hilir) in forest fireprevention efforts and land. The result of coordination that runs less than themaximum. This can be seen by the increasing number of land and forest thatburned from year to year.The concept of the theory is the theory that researcher use A. F. Stoonerin Ibnu Syamsi; a good and effective coordination can be seen from: planning,communication, division of tasks, supervisory. This study use squalitativeresearch methods to study this deskriptif. In collecting the data, the researcherused the interview techniques, observation and documentation. By using keyinformanst as a source of information and as a source triangulation techniques intesting the validity of tha data.Key words: Coordination, Forest Fires, DINAS KEHUTANAN